Development of wear resistant metal matrix composite coatings based on laser surfacing engineering technique / Moinuddin Mohammed Quazi - Moinuddin, Mohammed Quazi (2016)
Laser based additive manufacturing technology (LAM) comprising of Laser composite surfacing (LCS) technique has emerged as an alternative photon driven manufacturing technology for the fabrication of hybrid metal matrix composite coatings to enhance the mechanical and tribological properties of critical machinery components. To meet the application needs, instead of bulk material processing, surface coatings are rendered far more suitable and are often utilized in form of Hybrid metal matric composite coatings (HMMC). These coatings have great potential in the fabrication and regeneration of automotive, aerospace, defense and manufacturing components as protective hard facing self-lubricating wear resistant composite coating. Under the category of lightweight metals, self-lubricating coatings have eluded aluminium alloys and researchers have not realized the potential of optimization techniques for the laser processing parameters. This may dramatically increase the friction coefficient and wear rates of critical sliding components and the full potential of improvement in mechanical and surface properties are not realized. The present work explores the possibility to utilize several wear resistant metal matrixes composite (MMC) and hybrid (HMMC) coatings with the assimilation of various solid lubricants in these coatings blends to investigate their tribo-mechanical performance. In the first phase fabrication, characterization and optimization of Ni-WC based wear resistant MMC coatings was deposited on aluminium alloy AA5083. To achieve laser composite surfacing, an analysis on optimization of laser processing parameters was made, in order to improve the tribo-mechanical properties of aluminium alloy. To carry out the investigation, Taguchi optimization method using standard orthogonal array of L16 (34) was employed. Thereafter, the results were analyzed using signal to noise (S/N) ratio response analysis and Pareto analysis of variance (ANOVA). Finally, confirmation tests with the best parameter combinations obtained in the optimization process were made to demonstrate the progress made. Results showed that the surface hardness (953 Hv) and roughness (0.81m) of coated AA5083 samples were enhanced by 9.27%, and 13.14% respectively. Tribological behavior of LCS samples was investigated using ball-on-plate tribometer against a counter-body of hardened and tempered 440c bearing steel. It was revealed that the wear of the Ni-WC coated samples improved to around 2.5 times. For lower applied loads, coating exhibited abrasive wear mode and a reduction in plastic deformation. In the second phase, solid lubricant coating comprising of lamellar graphite and TiO2 was employed to fabricate Ni-WC based HMMC coatings on Al-Si hypereutectic piston alloy. The concentrations of both solid lubricants were varied in concentration of 5, 10, and 15 wt. % to identify their optimum concentration. Results indicated that the addition of graphite and TiO2 to fabricate HMMC was beneficial in reducing friction and wear of Ni-WC MMC coating. Furthermore, the hardness of both coatings was improved. The wear mechanism of MMC coating was transformed into mild abrasive and adhesive after the addition of both solid lubricants.